Less conservative optimal robust control of a 3-DOF helicopter - Buzachero, L. F.S.; Assunção, E. [UNESP]; Teixeira, M. C.M. [UNESP]; Silva, E. R. P. Da (Hindawi, 2015)
This work proposes an improved technique for design and optimization of robust controllers norm for uncertain linear systems, with state feedback, including the possibility of time-varying the uncertainty. The synthesis techniques used are based on LMIs (linear matrix inequalities) formulated on the basis of Lyapunov's stability theory, using Finsler's lemma. The design has used the addition of the decay rate restriction, including a parameter γ in the LMIs, responsible for decreasing the settling time of the feedback system. Qualitative and quantitative comparisons were made between methods of synthesis and optimization of the robust controllers norm, seeking alternatives with lower cost and better performance that meet the design restrictions. A practical application illustrates the efficiency of the proposed method with a failure purposely inserted in the system.